Kae1 Allelic Variants Affect torc1 Activation and Fermentation Kinetics in Saccharomyces Cerevisiae - Martinez-Fernandez, C; Salinas-Sanhueza, F; Kessi-Perez, E (Frontiers Media S.A., 2019)
[No abstract available]